Calcium ion regulation of sodium alginate in pure buckwheat noodles shown by in vitro simulated digestion - Wang, Hongyan; Zhang, Jiukai; Han, Lingyu; Cao, Jijuan; Yang, Jixin; Zhang, Ying; Hu, Bing (Frontiers in Nutrition, 2023)
The effects of calcium sodium alginate on quality and starch digestion of pure buckwheat noodles were investigated. The incorporation of calcium ions into noodles containing sodium alginate was found to reduce water absorption by the noodles during cooking, together with an increase of the turbidity. Calcium addition improved the noodle texture, as shown by the measurement of hardness, elasticity, adhesion, and chewability. In vitro simulations of digestion showed that calcium ion cross-linking with sodium alginate reduced glucose formation by approximately 23.3 mg/g. X-ray diffraction and Fourier transform infrared spectroscopy showed alterations in the crystal zone of the noodles induced by an alginate gel network, although no new chemical substances were generated. Noodles prepared by this exogenous method may be useful as functional foods for patients with diabetes.